2022
DOI: 10.1186/s12890-022-02063-2
|View full text |Cite
|
Sign up to set email alerts
|

Old age is associated with worse treatment outcome and frequent adverse drug reaction in Mycobacterium avium complex pulmonary disease

Abstract: Background The number of patients with nontuberculous mycobacterial pulmonary disease (NTM-PD) is rapidly increasing globally, especially in the older population. However, there is a dearth of evidence regarding the impact of aging on the treatment outcomes of NTM-PD. Methods We analyzed consecutive patients who satisfied the diagnostic criteria for Mycobacterium avium complex (MAC)-PD and received antibiotic treatment between January 2009 and Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 40 publications
1
7
0
Order By: Relevance
“…Despite the small group size, a more severe disease was noted in aged compared to young animals in the form of pulmonary consolidation and lesions, which is in line with established clinical literature [6163]. Increased lung damage in aged animals was also evident from histological analyses that revealed presence of lymphoid aggregates, interstitial fibrosis, pulmonary edema, and bronchopneumonia.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the small group size, a more severe disease was noted in aged compared to young animals in the form of pulmonary consolidation and lesions, which is in line with established clinical literature [6163]. Increased lung damage in aged animals was also evident from histological analyses that revealed presence of lymphoid aggregates, interstitial fibrosis, pulmonary edema, and bronchopneumonia.…”
Section: Discussionsupporting
confidence: 86%
“…One study from South Korea demonstrated that long-term treatment success rate decreased with age, particularly in patients aged=≥80 years. Whereas the rate of adverse drug reactions requiring discontinuation of treatment increased with age, and the number was twice as high in patients aged=≥80 years than in those aged=<50 years [17]. These findings support the decision to treat relatively younger patients where better treatment outcomes are expected with lesser side effects.…”
Section: Discussionmentioning
confidence: 90%
“…However, a previous study has shown that cavitation on CT imaging, the presence of night sweats, and weight loss were associated with treatment initiation [ 16 ]. One study from South Korea demonstrated that the long-term treatment success rate decreased with age, and the rate of adverse drug reactions requiring a discontinuation of treatment increased with age, particularly in patients aged ≥80 years [ 17 ]. These findings support the decision to treat relatively younger patients, where better treatment outcomes are expected with fewer side effects.…”
Section: Discussionmentioning
confidence: 99%